PENGARUH EKSTENSIFIKASI PAJAK, TINGKAT KEPATUHAN WAJIB PAJAK, DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN WAJIB PAJAK ORANG PRIBADI - Andyta Novasari; Dyah Ratnawati (BAJ: Behavioral Accounting Journal, 2020)
This research aims to find out what the impact of tax extensification, the level of compliance of taxpayers, and tax audits of income tax receipts (PPh) Personal Taxpayers. The focus of this research is KPP Pratama Surabaya Pabean Cantikan in year 2016 to 2018. The classification of this study is quantitative research. The sample used 36 data with using secondary data. The technique of determining the sample using boring sampling. The data research method of this study is multiple linear regression analysis using SPSS. The outcome from this research is the tax extensification and the level of compliance of taxpayers do not have an impact on the income taxpayers (PPh) of individual taxpayers, but tax audit has an impact on income tax receipts (PPh) of individual taxpayers.